2020
DOI: 10.1016/j.heliyon.2020.e04728
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular function and cortical and sub-cortical alterations in an aging population

Abstract: While it is well known that the vestibular system is responsible for maintaining balance, posture and coordination, there is increasing evidence that it also plays an important role in cognition. Moreover, a growing number of epidemiological studies are demonstrating a link between vestibular dysfunction and cognitive deficits in older adults; however, the exact pathways through which vestibular loss may affect cognition are unknown. In this cross-sectional study, we sought to identify relationships between ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 95 publications
(122 reference statements)
2
28
0
2
Order By: Relevance
“…Vestibular information from the semi-circular canals (SCC), otoliths, and nuclei is relayed through the thalamus to the hippocampus, entorhinal cortex, and basal ganglia. The red arrow points toward the ventral lateral nucleus, a putative subfield of the thalamus that receives vestibular input [48]. CAWorks (www.cis.jhu.edu/software/caworks) was used for visualization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vestibular information from the semi-circular canals (SCC), otoliths, and nuclei is relayed through the thalamus to the hippocampus, entorhinal cortex, and basal ganglia. The red arrow points toward the ventral lateral nucleus, a putative subfield of the thalamus that receives vestibular input [48]. CAWorks (www.cis.jhu.edu/software/caworks) was used for visualization.…”
Section: Methodsmentioning
confidence: 99%
“…semicircular canal and/or otolith organs) that contribute to those changes. Bridging these knowledge gaps, novel cross-sectional studies in healthy, older individuals found significant associations between age-related vestibular loss and gross atrophy of the hippocampus [2,48] and the entorhinal cortex [48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is unclear the rate of progression and how this reorganization is implemented. However, this idea is supported by compounding evidence emerging from neuroimaging studies showing that the age-related effects across sensory systems differ [73,74]. For example, deterioration of vestibular substrate has been welldocumented to be linked to volume reduction of vestibular nuclei in the brainstem and reduction of cerebellar volume [73].…”
Section: Quiet Stance Vpdis and Agingmentioning
confidence: 99%
“…However, this idea is supported by compounding evidence emerging from neuroimaging studies showing that the age-related effects across sensory systems differ [73,74]. For example, deterioration of vestibular substrate has been welldocumented to be linked to volume reduction of vestibular nuclei in the brainstem and reduction of cerebellar volume [73]. On the other hand, evidence of age-related changes in the visual cortex is primarily associated with functional aspects of neurons and neuronal communication in the visual system [70].…”
Section: Quiet Stance Vpdis and Agingmentioning
confidence: 99%